[PP.25.06] ACUTE EFFECTS OF AEROBIC AND RESISTANCE EXERCISES IN INFLAMMATORY MARKERS IL-10 AND IL-1RA IN PATIENTS WITH RESISTANT HYPERTENSION: RATIONALE OF A RANDOMIZED, CONTROLLED TRIAL. (September 2017) - Gasparetti, C.; Fraccari, N.; Ritter, A.M.; Modolo, R.; Brunelli, V.; Correa, N.; Coelho-Junior, H.; Rodrigues, B.; Moreno, H.; De Faria, A.P.
Abstract : Objective: The role of regular physical activity on blood pressure (BP) and inflammatory process have been investigated in hypertension. This study aims to evaluate the acute effects of either aerobic, resistance or both combined exercises on inflammatory markers IL-10 and IL-1ra in resistant (RH) and controlled hypertensive (HT) subjects. Secondly, we will assess those effects on BP levels. Design and method: This randomized, single-blind, crossover non-pharmacological intervention study will include 20 patients, 10 RH and 10 HT, who are regularly followed at the Outpatient Resistant Hypertension Clinic (UNICAMP, Brazil). This study will comprise two parts: (1) to determine the type and duration of each exercise individually for each volunteers, and (2) to perform all the three types of exercise in a crossover way in all subjects, which will consist of: 1) aerobic exercise: activity on a treadmill lasting 45 minutes with intensity of 50–60% of maximum heart rate obtained from ergometer test; 2) resistance exercise: 4 series of 12 repetitions of resistance exercises at moderate intensity (until moderate fatigue), for 45 minutes; 3) combined exercise: aerobic (25 minutes) + resistance (20 minutes), with an interval of 2 minutes between sessions totalizing 45 minutes. We will perform blood test before and after the interventions to assess inflammatory biomarkers IL-10 and IL-1ra. Also, we will determine the beat-to-beat BP levels (using the Finometer device). Figure. No caption available. Results: We expect that the acute practice of exercise modulates the inflammatory biomarkers, IL-10 and IL-1ra, and secondly, the BP levels. Conclusions: This study may provide a better understanding of the acute mechanisms of this non-pharmacologic treatment in RH, in order to make this more effective in this high-risk population.